Premarital childbearing in sub-Saharan Africa: Can investing in women's education offset disadvantages for children? - Emily Smith-Greenaway (Elsevier, 2016)
Premarital childbearing is common in many parts of sub-Saharan Africa, and may become increasingly so with the rise in women's age at first marriage. These trends are concerning given the severe childhood health consequences associated with being born premaritally. However, women's could condition the experience of having a premarital birth in a way that lessens its consequences for children. Extending the large literature on the child health benefits of mothers' education-including her educational attainment and acquisition of key educational skills - I analyze whether the consequences of being born premaritally are lessened among children whose mothers are more highly-educated. The study focuses on Malawi, a southeast African country where child mortality rates remain high. I use Demographic and Health Survey data to estimate discrete-time logistic regression models (N=30,411 children younger than age five) of the relationships between premarital childbearing, mothers' educational background, and child mortality. The findings confirm that though being born premaritally is associated with higher child mortality, this is only true for children whose mothers have never been to school or discontinued at the primary level and/or never learned how to read. There is no evidence that being born premaritally is associated with elevated mortality among children whose mothers have been to secondary school and/or know how to read. The results demonstrate that analyzing how premarital childbearing intersects with other sources of health inequality enhances our understanding of the circumstances under which it poses the greatest risk to child well-being in sub-Saharan Africa. Keywords: Child health, Child mortality, Premarital childbearing, Education, Literacy, Africa, Malawi